A Technological Innovativeness Measurement Framework: A Case Study of Technology Based Indonesian Companies - Leo Aldianto; Jann Hidajat Tjakraatmadja; Dwi Larso; Ina Primiana; Grisna Anggadwita (Gadjah Mada International Journal of Business, 2021)
The measurement of innovation has been developed by various previous studies with a specific focus and goal. However, the existing measurement framework still cannot be applied all that easily by companies in Indonesia for assessing, evaluating, and improving their innovations. This study aims to propose a measurement framework using a multiple case study approach. Cases were selected from companies in the pharmaceutical and information and communications technology (ICT) industries because they contribute substantially to the manufacturing sector and both are vital to Indonesia. The results of this study indicate that the measurement model of innovation consists of technological innovation and the management of technological innovation. There are three phases in the technological innovation process which include the initiation phase (conceiving ideas and acquiring information, then transforming it into knowledge), the development phase (validating knowledge and checking its appropriateness), and the diffusion phase (getting users' feedback and Go & scaling up). Meanwhile, the management of technological innovation consists of having a strategy, the necessary resources, and operation. The analytical generalization of this study is still considered to be limited, so further studies are needed to analyze cases in other industrial sectors. In addition, a quantitative study is required to construct a measuring instrument for the variables proposed in this study.